Investigation on tyre/road noise using ulster load tyre road assimilator - Hainin, Mohd. Rosli; Yaacob, Haryati; Woodside, Alan; Woodward, David (Faculty of Civil Engineering, 2008)
This paper describes the development of a laboratory test that can be used to evaluate the factors relating to the generation of tyre/road noise. An internal drum machine known as Ulster Load Tyre Road Assimilator(ULTRA), was used to assess different types of road surface using smooth and treaded tyres at different speed, loading and tyre pressure conditions. Speed was found to be the biggest factor to effect tyre/road noise followed by the presence of joints, surface texture depth, loading and tyre pressure. A smooth test tyre gives better correlation with texture depth compared to a treaded tyre. The new test methods developed have been shown to rank the materials assessed according to their expected in-service performance. The method provides the highway industry and specifying bodies a laboratory means of both ranking noise and for understanding the mechanisms involved in its generation.